2010
DOI: 10.1149/1.3374194
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin (AlCrTaTiZr)N[sub x]/AlCrTaTiZr Bilayer Structures with High Diffusion Resistance for Cu Interconnects

Abstract: In this study, ͑AlCrTaTiZr͒N 0.7 and ͑AlCrTaTiZr͒N 1 films with quinary metallic elements were developed as diffusion barrier materials for Cu interconnects. To improve the interface adhesion to Cu, an AlCrTaTiZr buffer layer was deposited on the barriers to form ͑AlCrTaTiZr͒N 0.7 /AlCrTaTiZr and ͑AlCrTaTiZr͒N 1 /AlCrTaTiZr bilayer structures. The as-deposited AlCrTaTiZr and ͑AlCrTaTiZr͒N 0.7 films were amorphous structures, and ͑AlCrTaTiZr͒N 1 possessed a nanocomposite structure. After annealing at 800°C, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In recent years, great efforts have been focused on HEA films prepared by the magnetron sputtering method, such as, TiVCrAlZrN x [7], (TiVCrZrHf)N [8], (AlCrMoTaTi)N [9], FeCoNiCuVZrAl [10], etc. It has been shown that these HEA films display many advantages in terms of both mechanical and physical properties, high hardness and wear resistance [11][12][13], high resistance to corrosion [14], and oxidation [15], and excellent thermal stability especially when used as diffusion barriers in copper metallization [16][17][18][19]. It is well-known that transition metal nitride coatings usually show high hardness, good thermal stability, and excellent wear resistance properties, which make them widely used as protective coatings in mechanical cutting tools at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great efforts have been focused on HEA films prepared by the magnetron sputtering method, such as, TiVCrAlZrN x [7], (TiVCrZrHf)N [8], (AlCrMoTaTi)N [9], FeCoNiCuVZrAl [10], etc. It has been shown that these HEA films display many advantages in terms of both mechanical and physical properties, high hardness and wear resistance [11][12][13], high resistance to corrosion [14], and oxidation [15], and excellent thermal stability especially when used as diffusion barriers in copper metallization [16][17][18][19]. It is well-known that transition metal nitride coatings usually show high hardness, good thermal stability, and excellent wear resistance properties, which make them widely used as protective coatings in mechanical cutting tools at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, owing to the thermodynamically stable solid-solution structures and severe lattice distortions of multiprincipal-element alloys (called high entropy alloys, HEAs) [17][18][19], individual films and bilayered structures of HEAs and HEA nitrides (denoted as HEANs) with a nanocomposite or amorphous structure and a thickness from 70 to as low as 10 nm have been developed as diffusion barriers [20][21][22]. These previous studies have shown that the multicomponent HEAN and/or HEA-based barrier materials (such as quinary (AlCrTaTiZr)N x ) sustained a high temperature of 800 • C for 30 min inhibiting Cu diffusion; this fact suggests that high stability of the interconnect structures in the thermal cycles in manufacturing (300-400 • C) and operation (100-200 • C) is retained for much longer time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that, by the multi-component-induced lattice distortions and the layered structure-caused interface mismatches, HEA and HEAN barriers such as senary AlCrRuTaTiZr and (AlCrRuTaTiZr)N and their stacking structures with a thickness down to only 4 nm presented an extreme resistance to the interdiffusion of Cu and Si 23 24 25 26 . Their high endurance temperature (almost 900°C) against interdiffusion suggests the high potential of HEAs and HEANs as very promising barriers for practical applications to Cu interconnects.…”
mentioning
confidence: 99%